Contribution of serotonin and dopamine to changes in core body temperature and locomotor activity in rats following repeated administration of mephedrone - Shortall, Sinead E.; Spicer, Clare H.; Ebling, Francis J.P.; Green, A. Richard; Fone, Kevin C.F.; King, Madelaine V. (Wiley, 2015)
The psychoactive effects of mephedrone are commonly compared to those of 3,4-methylenedioxymethamphetamine, but because of a shorter duration of action users often employ repeated administration to maintain its psychoactive actions. This study examined the effects of repeated mephedrone administration on locomotor activity, body temperature and striatal dopamine and 5-hydroxytryptamine (5-HT) levels, and the role of dopaminergic and serotonergic neurons in these responses. Adult male Lister hooded rats received three injections of vehicle (1ml/kg, i.p.) or mephedrone HCl (10mg/kg) at 2h intervals for radiotelemetry (temperature and activity) or microdialysis (dopamine and 5-HT) measurements. Intracerebroventricular pre-treatment (21 to 28 days earlier) with 5,7-dihydroxytryptamine (5,7-DHT, 150μg) or 6-hydroxydopamine (6-OHDA, 300μg) was used to examine the impact of 5-HT or dopamine depletion on mephedrone-induced changes in temperature and activity. A final study examined the influence of i.p. pre-treatment (-30min) with the 5-HT1A receptor antagonist WAY-100635 (0.5mg/kg), 5-HT1B receptor antagonist GR 127935 (3mg/kg) or the 5-HT7 receptor antagonist SB-258719 (10mg/kg) on mephedrone-induced changes in locomotor activity and rectal temperature. Mephedrone caused rapid-onset hyperactivity, hypothermia (attenuated on repeat dosing), and increased striatal dopamine and 5-HT release following each injection. Mephedrone-induced hyperactivity was attenuated by 5-HT depletion and 5-HT1B receptor antagonism, whereas the hypothermia was completely abolished by 5-HT depletion and lessened by 5-HT1A receptor antagonism. These findings suggest that stimulation of central 5-HT release and/or inhibition of 5-HT reuptake play a pivotal role in both the hyperlocomotor and hypothermic effects of mephedrone, which are mediated in part via 5-HT1B and 5-HT1A receptors.